THE ROLE OF MOTIVATION IN STUDENTS' COGNITION - Z. D. Abralova; G. S. Solijonova (Bright Mind Publishing, 2025)
This article analyzes the impact of motivation on students' activity from both theoretical and practical perspectives. It explores the concept of motivation, its key theories (Maslow, Deci & Ryan, Skinner), and the factors influencing students' motivation. Additionally, effective strategies for enhancing motivation, such as interactive teaching methods and reward systems, are examined based on scientific research.
Keywords: Motivation, interactive teaching methods, reinforcement, intrinsic motivation, Maslow, Deci and Ryan, autonomy, competence, relatedness, Skinner.